Dental Residents’ Knowledge and Attitude towards Stem Cells and Regenerative Dentistry - Rahavi Ez-Abadi, Akram; Ebn Ahmady, Arezoo; Tabatabaei, Fahimeh S. (Journal of Dental School, 2019)
Objectives: Success of regenerative dental procedures highly depends on their acceptance by the clinicians; yet, little is known about dental residents’ attitudes regarding this new technology. The purpose of this study was to assess the knowledge and attitude of post-graduate dental students towards stem cells and regenerative dentistry as part of future dental treatments. Methods: This cross-sectional survey was conducted on 84 third-year residents of various dental specialties. The questionnaire included demographics and professional status of the respondents, questions regarding their ethical beliefs and their clinical practice. Results: Eighty-four completed questioners were returned anonymously. The majorities of the participants were female, and had practiced for ≤ 5 years. The survey showed that 76.2% of the participants had not received any continuing education or training courses on stem cells or regenerative dentistry. The majority of the participants (82.1%) believed that regenerative treatments should be included in dental practice. Of all, 76.2% had no umbilical cord or stem cell banking for themselves or a relative and 63.1% thought that dental pulp stem cell banking would be useful to regenerate dental tissues. Most of the participants (65.5%) had never performed regenerative therapy of any kind in their clinical practice and 51.2% of the participants were not sure whether regenerative procedures would be successful. Conclusion: Although more evidence on the efficacy and safety of regenerative dentistry is required, postgraduate training in this regard seems necessary.